Microglia modulate proliferation, neurite generation and differentiation of human neural progenitor cells - Lilienberg, Julianna; Apáti, Ágota; Réthelyi, János M.; Homolya, László (Frontiers in Cell and Developmental Biology, 2022)
Microglia, the primary immune cells of the brain, significantly influence the fate of neurons after neural damage. Depending on the local environment, they exhibit a wide range of phenotypes, including patrolling (naïve), proinflammatory, and anti-inflammatory characteristics, which greatly affects neurotoxicity. Despite the fact that neural progenitor cells (NPCs) and hippocampal neurons represent cell populations, which play pivotal role in neural regeneration, interaction between microglia and these cell types is poorly studied. In the present work, we investigated how microglial cells affect the proliferation and neurite outgrowth of human stem cell-derived NPCs, and how microglia stimulation with proinflammatory or anti-inflammatory agents modulates this interaction. We found that naïve microglia slightly diminish NPC proliferation and have no effect on neurite outgrowth. In contrast, proinflammatory stimulated microglia promote both proliferation and neurite generation, whereas microglia stimulated with anti-inflammatory cytokines augment neurite outgrowth leaving NPC proliferation unaffected. We also studied how microglia influence neurite development and differentiation of hippocampal dentate gyrus granule cells differentiated from NPCs. We found that proinflammatory stimulated microglia inhibit axonal development but facilitate dendrite generation in these differentiating neurons. Our results elucidate a fine-tuned modulatory effect of microglial cells on cell types crucial for neural regeneration, opening perspectives for novel regenerative therapeutic interventions.